Evaluating Superoxide Dismutase (SOD), Glutathione (GSH), Malondialdehyde (MDA) and the Histological Changes of the Lung Tissue after γ-Irradiation in Rats - Abolhasan Rezaeyan; Gholam Hassan Haddadi; Massood Hosseinzadeh (Fasa University of Medical Sciences, 2016)
Background & Objective: The lung is a radiosensitive organ and its damage is a dose-limiting factor in radiotherapy. Different side effects such as pneumonia and lung fibrosis are found in patients with thorax irradiation. The objective of the present study is to evaluate the effects of γ-irradiation on acute and chronic injuries of lung tissue in rats. Materials & Methods: 32 rats were divided into two groups. Control group consisted of 14 rats that underwent shame irradiation. In radiation group, 18 rats underwent γ-irradiation. The rats were exposed to γ-irradiation 18 Gy using a single fraction cobalt-60 unit. Eight rats in each group were sacrificed 24 hours after radiotherapy for determining Superoxide Dismutase (SOD), Glutathione (GSH), Malondialdehyde (MDA), and histopathological evaluations. Remained animals were sacrificed eight weeks after radiotherapy for histopathological evaluation. Results: Compared to control group, the level of SOD and GSH significantly decreased and MDA level significantly increased in radiation group 24 hours following irradiation, (p=0.001, p<0.001, p=0.001) respectively. Early histopathological results after 24 hours showed that radiation increases neutrophil, macrophage, and inflammation incidence compared to control group (p<0.05). Late histopathological evaluation after eight weeks revealed significant increase in factors including mast cells, pulmonary edema, vascular thickness, vascular damage, and also inflammation and fibrosis incidence in case group compared to radiation group  (p<0.05). Conclusion: Localized chest radiation with dose of 18 Gy induces changes in oxidative stress indices and histopathological lung tissue damage in short and long term.